Respuesta :
Answer:
[tex]\displaystyle \frac{dy}{dt} = \frac{-3}{2(4t- 3)^2\sqrt{\frac{t}{4t - 3}}}[/tex]
General Formulas and Concepts:
Calculus
Differentiation
- Derivatives
- Derivative Notation
Derivative Property [Multiplied Constant]: [tex]\displaystyle \frac{d}{dx} [cf(x)] = c \cdot f'(x)[/tex]
Derivative Property [Addition/Subtraction]: [tex]\displaystyle \frac{d}{dx}[f(x) + g(x)] = \frac{d}{dx}[f(x)] + \frac{d}{dx}[g(x)][/tex]
Basic Power Rule:
- f(x) = cxⁿ
- f’(x) = c·nxⁿ⁻¹
Derivative Rule [Quotient Rule]: [tex]\displaystyle \frac{d}{dx} [\frac{f(x)}{g(x)} ]=\frac{g(x)f'(x)-g'(x)f(x)}{g^2(x)}[/tex]
Derivative Rule [Chain Rule]: [tex]\displaystyle \frac{d}{dx}[f(g(x))] =f'(g(x)) \cdot g'(x)[/tex]
Step-by-step explanation:
Step 1: Define
Identify
[tex]\displaystyle y = \sqrt{\frac{t}{4t - 3}}[/tex]
Step 2: Differentiate
- Basic Power Rule [Derivative Rule - Chain Rule]: [tex]\displaystyle y' = \frac{1}{2\sqrt{\frac{t}{4t - 3}}} \cdot \frac{d}{dt} \bigg[ \frac{t}{4t - 3} \bigg][/tex]
- Derivative Rule [Quotient Rule]: [tex]\displaystyle y' = \frac{1}{2\sqrt{\frac{t}{4t - 3}}} \cdot \frac{(t)'(4t - 3) - t(4t - 3)'}{(4t - 3)^2}[/tex]
- Basic Power Rule [Derivative Properties]: [tex]\displaystyle y' = \frac{1}{2\sqrt{\frac{t}{4t - 3}}} \cdot \frac{(4t - 3) - 4t}{(4t - 3)^2}[/tex]
- Simplify: [tex]\displaystyle y' = \frac{-3}{2(4t- 3)^2\sqrt{\frac{t}{4t - 3}}}[/tex]
Topic: AP Calculus AB/BC (Calculus I/I + II)
Unit: Differentiation